High-Resolution Angioscopic Imaging During Endovascular Neurosurgery. Issue 2 (23rd April 2014) - McVeigh, Patrick Z.; Sacho, Raphael; Weersink, Robert A.; Pereira, Vitor M.; Kucharczyk, Walter; Seibel, Eric J.; Wilson, Brian C.; Krings, Timo
Abstract: BACKGROUND: Endoluminal optical imaging, or angioscopy, has not seen widespread application during neurointerventional procedures, largely as a result of the poor imaging resolution of existing angioscopes. Scanning fiber endoscopes (SFEs) are a novel endoscopic platform that allows high-resolution video imaging in an ultraminiature form factor that is compatible with currently used distal access endoluminal catheters. OBJECTIVE: To test the feasibility and potential utility of high-resolution angioscopy with an SFE during common endovascular neurosurgical procedures. METHODS: A 3.7-French SFE was used in a porcine model system to image endothelial disruption, ischemic stroke and mechanical thrombectomy, aneurysm coiling, and flow-diverting stent placement. RESULTS: High-resolution, video-rate imaging was shown to be possible during all of the common procedures tested and provided information that was complementary to standard fluoroscopic imaging. SFE angioscopy was able to assess novel factors such as aneurysm base coverage fraction and side branch patency, which have previously not been possible to determine with conventional angiography. CONCLUSION: Endovascular imaging with an SFE provides important information on factors that cannot be assessed fluoroscopically and is a novel platform on which future neurointerventional techniques may be based because it allows for periprocedural inspection of the integrity of the vascular system and the deployed devices. In addition, it may be of diagnostic use for inspecting the vascular wall and postprocedure device evaluation.